2009
DOI: 10.2478/v10009-009-0047-z
|View full text |Cite
|
Sign up to set email alerts
|

Riverine water transformation during retention in small lowland reservoirs

Abstract: Six small dam reservoirs in northeastern Poland, with different hydrologic and catchment characteristics were selected for research from March to October (2001October ( -2003. There was a significant correlation between DOC and TP in the reservoirs and the water retention time (WRT). The highest values of electrical conductivity (EC) were recorded in reservoirs with an agricultural basin. In almost all reservoirs a statistically significant decrease of EC, compared to inflowing waters, was noted. Nitrates were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…(2008) showed that hydrology, climatic forcing and retention time are major forcing functions that promote water circulation (vertical and horizontal) in the reservoir and most likely having a strong effect on dissolved and particulate material distribution. Small reservoirs with short water retention times could contribute to the reduced nutrient retention and also could control biological processes, as discussed by Suchowolec and Górniak (2009), based on research on six small reservoirs in Poland.…”
Section: Discussionmentioning
confidence: 99%
“…(2008) showed that hydrology, climatic forcing and retention time are major forcing functions that promote water circulation (vertical and horizontal) in the reservoir and most likely having a strong effect on dissolved and particulate material distribution. Small reservoirs with short water retention times could contribute to the reduced nutrient retention and also could control biological processes, as discussed by Suchowolec and Górniak (2009), based on research on six small reservoirs in Poland.…”
Section: Discussionmentioning
confidence: 99%
“…However despite the relatively high content of organic matter in sediments, the mean concentration of PO4 -3 in interstitial water was the lowest among the reservoirs studied. Humic substances, abundant in this reservoir, have strong complexing properties and immediately bind orthophosphate released from decomposition of fresh organic matter (Gorniak 1995;Górniak, Jekatierynczuk-Rudczyk 2006;Suchowolec, Górniak 2009). Spatial coexistence of a high content of TP and a low concentration of PO4 -3 in the sediment of Siemianówka confirms the phenomenon of binding phosphate into humic complexes in the sediment, which immobilizes phosphorus.…”
Section: Discussionmentioning
confidence: 99%
“…In reservoirs with longer HRTs, particle sedimentation of adsorbed phosphorus increases and algae and bacteria further consume dissolved phosphorus. In contrast, phosphorus retention is lower in new reservoirs without a buffer plant zone (Suchowolec and Gorniak, 2009). When hydropower stations generate electricity, they must discharge floods for safety; therefore, the HRT will be much shorter than that of reservoirs.…”
Section: Influence Of Storage Capacity and Hydraulic Residence Timementioning
confidence: 99%